Role of Student Psychology in Thinking Style and Teaching with Style of Lectures at Higher Education in Indonesia - Hasanuddin; Salamiah Sari Dewi; Erlina Sari Siregar, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The teaching method is crucial to the quality of education in any institution. The Indonesian institutions of higher education struggle with teaching quality and student success. The Indonesian Ministry of Higher Education has obstacles regarding student performance. Determining the role of student psychology in the relationship between teaching quality and learner performance at Indonesian Universes necessitated the development of a conceptual framework. The quantitative technique approach and partial least square (PLS) were implemented in this work to determine the findings. The research suggested that teachers should focus on the psychology of the students to improve their thinking and teaching styles. This study's focus is confined to Indonesian institutions of higher education. Notably, no previous research has presented theoretical and practical consequences on this topic in the existing literature. Therefore, this study has significant implications for literature and school administration in Indonesia to improve students' performance. In addition to the theoretical and practical consequences, this study identifies different gaps in the literature that future scholars must investigate.